2020
DOI: 10.1002/mrm.28319
|View full text |Cite
|
Sign up to set email alerts
|

Genetic algorithm search for the worst‐case MRI RF exposure for a multiconfiguration implantable fixation system modeled using artificial neural networks

Abstract: Purpose This paper presents a method to search for the worst‐case configuration leading to the highest RF exposure for a multiconfiguration implantable fixation system under MRI. Methods A two‐step method combining an artificial neural network and a genetic algorithm is developed to achieve this purpose. In the first step, the level of RF exposure in terms of peak 1‐g and/or 10‐g averaged specific absorption rate (SAR1g/10g), related to the multiconfiguration system, is predicted using an artificial neural net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The entire applied process relied on electromagnetic simulations, and, recently, in order to avoid the required computational time and memory requirements, novel machine learning methods have been proposed for the assessment of MRI RF heating. Specifically, the application of neural networks has been proposed to predict the worst-case heating of orthopedic fixation plates in the MRI environment, with the only input being the geometric properties of the implant [57]. Additionally, deep learning has been applied to predict the SAR values at the tip of conductive leads along clinically relevant cardiac and DBS paths during 1.5 T and 3 T MRI [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…The entire applied process relied on electromagnetic simulations, and, recently, in order to avoid the required computational time and memory requirements, novel machine learning methods have been proposed for the assessment of MRI RF heating. Specifically, the application of neural networks has been proposed to predict the worst-case heating of orthopedic fixation plates in the MRI environment, with the only input being the geometric properties of the implant [57]. Additionally, deep learning has been applied to predict the SAR values at the tip of conductive leads along clinically relevant cardiac and DBS paths during 1.5 T and 3 T MRI [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-assessment of heating is essential to determine the risk/benefit ratio of MRI exams in these patients and is typically performed through phantom experiments or full-wave electromagnetic simulations both of which being substantially time-consuming. Machine learning has been recently proposed as a promising tool for fast screening and determination of worst-case heating scenarios of orthopedic implants in MRI enviromnent [ 16 , 17 ]. Here we report results of a proof-of-concept simulation study to assess the applicability of machine learning to predict RF heating of elongated implants, such as leads in active electronic devices, during MRI at 1.5 T. We tested the hypothesis that a feedforward neural network could be trained to predict the local SAR at tips of implanted leads when only the knowledge of lead’s trajectory within the MRI RF coil and the features of RF coil are at hand.…”
Section: Discussionmentioning
confidence: 99%
“…Novel machine learning methods have been recently proposed as a paradigm shift in the assessment of MRI RF heating. Pioneering work by Chen group has shown that neural networks can predict the worst-case heating of orthopedic fixation plates in MRI environment when only the knowledge of implant’s geometrical features is at hand [ 16 , 17 ]. In their work, however, the implant’s position was predetermined within the MRI RF coil and thus, the effect of variation in electric field exposure due to changes in implant’s location and orientation was not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has employed machine learning (ML) to predict subject-specific local specific absorption rate (SAR) from B 1 + maps [ 9 ] and SAR distributions from anatomical MRI images [ 10 ]. Neural networks (NNs) have also been utilized to predict SAR during MRI of orthopedic fixation plates based on their geometric features [ 11 ], [ 12 ]. Our group has previously trained a NN to predict trajectory-specific SAR of DBS leads using the distribution of the tangential component of the incident electric field along each lead trajectory [ 1 ], [ 13 ].…”
Section: Introductionmentioning
confidence: 99%